Women’s Employment in Turkey’s ICT Sector: An Examination From a Social Inclusion Perspective - GÖRKEY, SELDA (IGI Global, 2022)
Women constitute one of the risk groups vulnerable to poverty; therefore, enabling their participation in the labor force is crucial to promoting social inclusion in a society. Employment in the information and communication technology (ICT) sector is widely known for being male-dominated, and recently women’s participation has become an important subject. This chapter aims to examine women’s employment in Turkey’s ICT sector from 2009 to 2016, from a social inclusion perspective, by using various indicators. Comparisons with European Union (EU) countries provide perspective on tracking the progress of employment structure and education choices for ICT by gender. All indicators signify the existence of a gender gap resulting in low rates of inclusion of women in Turkey’s ICT employment during the period. Examination of the reasons leads to making some policy recommendations to promote social inclusion of women in Turkey’s ICT employment. © 2022 by IGI Global. All rights reserved.
Source Title: Research Anthology on Changing Dynamics of Diversity and Safety in the Workforce
Keywords: Information and Communication Technology (ICT)